2003
DOI: 10.1038/sj.ejcn.1601534
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the prevalence of stunting, overweight and obesity amongst South African primary school children: a possible nutritional transition?

Abstract: Caution must be applied when using either definition for obesity. However, very high levels of agreement occur for overweight. There is no obvious relationship between overweight and stunting in this study, but high levels of mild stunting were observed. Regular clinical and epidemiological monitoring of nutritional status needs to be undertaken in South Africa to examine possible future trends of overweight/obesity and their relationship with stunting, and for comparisons with global trends.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 11 publications
6
67
1
Order By: Relevance
“…The South African National Primary Schools' Anthropometric Survey (Department of Health, 1994;Jinabhai et al, 2003) used data from South African children sampled in 1994 and the second used data from South African children sampled in -2004(Armstrong et al, 2006.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The South African National Primary Schools' Anthropometric Survey (Department of Health, 1994;Jinabhai et al, 2003) used data from South African children sampled in 1994 and the second used data from South African children sampled in -2004(Armstrong et al, 2006.…”
Section: Methodsmentioning
confidence: 99%
“…Urbanization and poor screening for inclusion in nutritional supplementation programs are thought to be the main causes of the coexistence of conditions associated with lack of nutritional resources and those associated with excess (Uauy and Kain, 2002;Jinabhai et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The burden of noncommunicable diseases is growing in South Africa where a complex mix of both overnutrition and undernutrition can be found (2) . This has resulted in nutrition-related conditions such as underweight and overweight/obesity coexisting in South African primary schools (3) .…”
mentioning
confidence: 99%
“…Compared with other studies that identified childhood overweight and obesity using weight-for-height Z-score cut-off points, the prevalence of overweight and obesity in children from this population is low in relation to other developing and developed countries and similar to that observed in less developed countries in Latin America 4,[23][24][25] . One study conducted in Argentina reported an obesity prevalence in children aged 24-72 months of 7.03%, ranging from 2.3% to 17.0%.…”
Section: Discussionmentioning
confidence: 50%